Influence of bodily resonances on emotional prosody perception - Selosse, Garance; Grandjean, Didier; Ceravolo, Leonardo (Frontiers in Psychology, 2022)
Emotional prosody is defined as suprasegmental and segmental changes in the human voice and related acoustic parameters that can inform the listener about the emotional state of the speaker. While the processing of emotional prosody is well represented in the literature, the mechanism of embodied cognition in emotional voice perception is very little studied. This study aimed to investigate the influence of induced bodily vibrations—through a vibrator placed close to the vocal cords—in the perception of emotional vocalizations. The main hypothesis was that induced body vibrations would constitute a potential interoceptive feedback that can influence the auditory perception of emotions. It was also expected that these effects would be greater for stimuli that are more ambiguous. The ambiguity was manipulated by the modulation of auditory perception, since the emotional vocalizations varied in their acoustic intensity from low-intensity vocalizations, considered as ambiguous, to high-intensity ones, considered as non-ambiguous. A significant effect of the vibrations was observed on the three behavioral indexes—discrimination, confusion and accuracy—with vibrations confusing rather than facilitating vocal emotion processing. Over all, this study brings new light on a poorly documented topic, namely the potential use of vocal cords vibrations as an interoceptive feedback allowing humans to modulate voice production and perception during social interactions.